Quality of Cardiopulmonary Resuscitation in Emergency Department Based on the AHA 2015 Guidelines; a Brief Report - Vafaei, Ali; Shams Akhtari, Amin; Heidari, Kamran; Hosseini, Somayeh (Archives of Academic Emergency Medicine, 2018)
Introduction: Adhering to existing guidelines on cardiopulmonary resuscitation (CPR) can increase the survival rate of the patients. The present study has been designed with the aim of determining the quality of CPR performed in the emergency department based on the latest protocol by the American heart association (AHA). Methods: In this prospective cross-sectional study CPR process was audited in patients above 18 years old in need of CPR presenting to the emergency departments of 3 teaching hospitals based on the AHA 2015 guidelines. Less than 60% agreement was considered as fail, 60-70% as poor, 70-80% as moderate, 80-90% as good, and 90-100% as excellent. Results: 80 cases of CPR were audited (55% male). Location of arrest was the hospital in 58 (72.5%) cases and 48 (60.0%) of the cases happened during the day. 28 (35.0%) cases had orotracheal intubation before the initiation of CPR. 30 (37.5%) patients had a shockable rhythm at the initiation of CPR. Based on the findings, out of the 31 studied items, 9 (29.03%) had excellent agreement, 10 (32.25%) had good, 4 (12.90%) had moderate, 2 (6.45%) had poor, and 6 (19.35%) had fail agreement rate. Conclusion: Based on the findings of the present study, the quality of applying the principles of basic and advanced CPR in the emergency department of the studied hospital had intermediate, poor and fail agreement with the recommendations of the AHA 2015 in at least one third of the cases.